2022
DOI: 10.1177/00938548221140351
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Interventions for Individuals who Committed Sexual Offenses Against Children: Development, Evaluation, and Implementation

Abstract: Web-based interventions (WBIs) have become increasingly important in mental health treatment. At the same time, WBIs for individuals who committed sexual offenses against children (ICSOC) are increasingly being developed and implemented. Despite this trend, it is unclear which treatment components make WBIs for ICSOC effective and what needs to be considered for successful implementation. Moreover, only few evaluation studies are available. The goal of this viewpoint paper, that includes a comprehensive litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In the fifth article, Schröder and colleagues (2023) performed a review of the literature on current web-based interventions for individuals who committed sexual offenses against children or who have a sexual interest in children. The literature review identified six web platforms, five of which were developed in the last 5 years.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…In the fifth article, Schröder and colleagues (2023) performed a review of the literature on current web-based interventions for individuals who committed sexual offenses against children or who have a sexual interest in children. The literature review identified six web platforms, five of which were developed in the last 5 years.…”
Section: Overview Of the Special Issuementioning
confidence: 99%